1994
DOI: 10.1148/radiology.191.3.8184078
|View full text |Cite
|
Sign up to set email alerts
|

Method for reducing scatter radiation dose to the contralateral breast during tangential breast irradiation therapy.

Abstract: Reduction in unwanted scatter dose to the contralateral breast is in accord with the philosophy of keeping radiation exposure as low as reasonably achievable and might be of most benefit for young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The relative dose decreases initially with depth, reaching a minimum at the depth of central ray peak dose d max . These characteristics are in agreement with results found by others [2, 42]. Studies showed that the out-of-field dose is qualitatively similar in behavior and of the same order of magnitude for all the treatment machines studied [2, 43-45].…”
Section: Discussionsupporting
confidence: 92%
“…The relative dose decreases initially with depth, reaching a minimum at the depth of central ray peak dose d max . These characteristics are in agreement with results found by others [2, 42]. Studies showed that the out-of-field dose is qualitatively similar in behavior and of the same order of magnitude for all the treatment machines studied [2, 43-45].…”
Section: Discussionsupporting
confidence: 92%
“…These characteristics agree with results found by others. 5,20,31 Studies have shown that the out-of-field dose is qualitatively similar in behavior and of the same order of magnitude for all the treat- ment machines studied. 5,[32][33][34] The scatter radiation outside the field edge consists mainly of low-energy photons and electron contamination.…”
Section: Resultsmentioning
confidence: 81%
“…14 Several groups have suggested that a far less thick lead shield might have significant protective effect. 15,16 In a series of phantom measurements, we found that the majority of contralateral dose is blocked by a few millimeters of lead. In a series of patients age 50 and less, we have tested lead shields for both tolerability and efficacy using both half-beam blocked and posteriorly aligned tangential fields.…”
mentioning
confidence: 89%